PERBANDINGAN LAMANYA PELEPASAN TALI PUSAT ANTARA PERAWATAN TALI PUSAT BASAH DAN PERAWATAN TALI PUSAT KERING PADA BAYI BARU LAHIR DI BPM RUSMIATI OKTA - Sri Yulia Ningsih; Maryani M. Imron (Jurnal Kesehatan Abdurrahman, 2012)
Cord care is a nursing action aims to treat the umbilical cord in newborn and prevent infection. Due to the Infant Mortality Rate (IMR) in Indonesia is still high one of them caused by neonatal infection, so that the correct treatment of the umbilical cord and both are neded to reduce the risk of infection and reduce IMR. Formulasi of the problem in this study is “ Are there any Difeference Between Umbilical Cord length release Umbilical Cord Care Wet and Dry in Newborn”. This study aims to determine the differences between wet umbilical cord care and dry care of neonatal in duration of release it. This study uses primary and secondary data with accidental sampling in wich new mother who do postpartum visit in BPM Rusmiati Okta totaling 34 people, statistical test used were t test. Research instrument using a check list. The result showed that the obtained p value of 0,000, the respondents who did wet cord care by 50%, ie an average of 8 days off = 76,5%. Respondents who did dry cord care by 50% with an average lenghth release 5 days = 58,8%, this means that there is no comparison between the length of the release of the umbilical cord wet and dry treatments, advised on health workers to perform a dry cord care in newborn.